Effect of a smartphone self-management digital support system for low-back pain (selfBACK) among workers with high physical work demands - secondary analysis of a randomized controlled trial - Charlotte Diana Nørregaard Rasmussen; Louise Fleng Sandal; Andreas Holtermann; Mette Jensen Stochkendahl; Paul Jarle Mork; Karen Søgaard (Nordic Association of Occupational Safety and Health (NOROSH), 2024)
OBJECTIVE: This study aimed to investigate whether physical work demands modify the effect of the selfBACK app, which is designed to support self-management of low-back pain. METHODS: In a secondary analysis of the selfBACK trial with 346 employed participants, we stratified into low (N=165) and high physical work demands (N=181). Outcomes included the Roland-Morris Disability Questionnaire (0-24), a numeric rating scale for low-back pain intensity (0-10), the Pain Self-Efficacy Questionnaire (0-60), and work ability (0-10). Intervention effects were assessed at three- and nine-month follow-ups using a linear mixed model. RESULTS: At three months, high physical demand workers with selfBACK showed a significant reduction in pain intensity [-0.8, 95% confidence interval (CI) -1.3- -0.2] compared to usual care. By nine months, the high physical demands workers with selfBACK reported reduced pain-related disability (-1.4, 95% CI -2.7- -0.1), improved pain self-efficacy (3.5, 95% CI 0.9-6.0), and lower pain intensity (-1.0, 95% CI -1.6- -0.4) compared to usual care. Low physical demands workers with selfBACK also improved pain self-efficacy [2.8 (95% CI 0.3-5.3)] compared to usual care. The impact of selfBACK was more noticeable among workers with high physical demands compared to their low physical demand counterparts, but no statistically significant differences were found in any outcome. CONCLUSIONS: The selfBACK intervention had consistent effects across workers with high and low physical work demands, indicating that these demands did not modify its impact. Both groups experienced similar positive effects, highlighting the intervention's effectiveness across varying levels of physical work demands.